MUSP 운동치료와 전기치료가 척추측만증환자의 Cobb's angle, 유연성, 균형능력 및 흉곽확장에 미치는 효과 비교 - 정기훈; 김은영; Jeong, Gihoon; Kim, Eunyoung (Journal of the Korean Society of Integrative Medicine, 2016)
PURPOSE : The purpose of this study to suggest the exercise programs for improving the function and structure by applying the Masan university scoliosis program exercise method and electrical therapy method to the scoliosis patient. METHODS : The subjects were 18 patients who were diagnosed with scoliosis. They were randomly assigned either to a Masan university scoliosis program exercise group (n=11) that received Masan university scoliosis program exercise program or to a electrical therapy group (n=7). Flexibility, static balance, dynamic balance, and spinal angles were measured by using one leg standing with closed eyes, functional reach test, and Cobb's angle, respectively. The chest expansion were calculated using differences of chest circumference between maximum inspiration and maximum expiration. RESULT : Masan university scoliosis program group before and after the intervention there was a difference in the static balance, spine angle(p<.05). Masan university scoliosis program group before and after the intervention there was a difference in the flexibility, static balance, spine angle, chest expansion (p<.05). CONCLUSION : These results revealed that Masan university scoliosis program exercise program improved flexibility, static standing balance, spine angle, used as scoliosis management and intervention. Therefore, it is expected to be used as a method for the treatment and prevention in the process of rehabilitation of patients with scoliosis.